Expert consensus for respiratory physiotherapy management of mechanically ventilated adults with community-acquired pneumonia: A Delphi study - van der Lee, L.; Hill, Anne-Marie; Patman, S. (Wiley-Blackwell Publishing, 2018)
Rationale and aims: Patients with community-acquired pneumonia (CAP) are frequently admitted to an intensive care unit. Physiotherapy may be provided to optimize respiratory function; however, there is significant variability in clinical practice and limited research directing best practice for this cohort. This study aimed to determine expert consensus for best physiotherapy practice for invasively ventilated adults with CAP. Method: A modified Delphi technique involved an international expert panel completing three rounds of an online questionnaire. The initial 35-statement questionnaire, based on a systematic literature review and survey of current clinical practice, covered physiotherapy assessment and treatment of intubated patients with CAP. Quantitative data using Likert scales determined level of agreement, with qualitative data collected through open-ended responses. Consensus threshold was set a priori at 70%. Items not achieving consensus were modified and new items added based on themes from qualitative data. Quantitative data were analysed descriptively, with thematic analysis used on qualitative data. Results: The panel comprised 29 international clinical and academic experts in critical care physiotherapy. Response rate was more than 95% for each round. Outcome achieved was 38 consensus statements covering assessment and treatment, with 28 statements (74%) providing consensus on recommended clinical practice, two consensus disagreement statements (7%) for what practice is not recommended, and eight statements (21%) indicating which treatments may be beneficial. Conclusion: Expert consensus regarding physiotherapy for intubated adults with CAP patients provides an evidence-based approach to guide clinical practice. The consensus statements can also be used to guide research evaluating physiotherapy interventions for patients with CAP.